1982
DOI: 10.1111/j.1365-3024.1982.tb00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune recognition of Echinococcus granulosus. 1. Parasite‐activated, primary transformation by normal murine lymph node cells

Abstract: Culture of murine lymph node cells together with living protoscolices of Echinococcus granulosus is described. The presence of the parasite induced potent blastic transformation in lymphocytes of unimmunized mice as indicated by tritiated thymidine incorporation. The response was markedly reduced by killing the parasite immediately prior to culture. No blastogenic activity was detectable in supernatants from living parasites cultured alone. Protoscolices from artificially infected syngeneic mice were effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Several researchers have suggested that the host's capacity for developing a parasite-specific cellular response able to eliminate the parasite may be modulated by parasite- derived effector substances (9,36,82). Local immune modulation by the parasite has been shown to enhance susceptibility to mycobacterial infections close to the site of parasite lesions (39).…”
Section: Immunology Definitive Hostsmentioning
confidence: 99%
“…Several researchers have suggested that the host's capacity for developing a parasite-specific cellular response able to eliminate the parasite may be modulated by parasite- derived effector substances (9,36,82). Local immune modulation by the parasite has been shown to enhance susceptibility to mycobacterial infections close to the site of parasite lesions (39).…”
Section: Immunology Definitive Hostsmentioning
confidence: 99%
“…The coenurus of Taenia multiceps produces a substance which stimulates mitosis in naive murine CD4+ T‐cells by a Class‐II‐restricted, macrophage‐dependent signal (26). Similar activity in Echinococcus granulosus (27) has been associated with the generation of CD8+ T cells suppressive for ConA‐activated mitosis (28). Secretions of M. corti , T. multiceps and E. multilocularis are all capable of modifying the accessory activity of murine macrophages (3,26,29).…”
Section: Resultsmentioning
confidence: 68%
“…EMT is a frequent feature in patients with lung fibrosis caused by other factors. Hydatid cyst fluid from E. granulosus is known to have significant effects on a variety of host immune cells, from acting as a mitogen, non‐specifically stimulating lymphocyte proliferation, to altering accessory cell function and antigen processing . It has also been shown to modify the phenotype of cells such as monocytes .…”
Section: Discussionmentioning
confidence: 99%